KOMUNIKASI INTERPERSONAL PEMBINA DALAM PEMBENTUKAN KARAKTER DIRI SANTRI (Studi pada Pondok Pesantren Al–Azkiya Kecamatan Keritang Kabupaten Indragiri Hilir) - Fadila, Nur; Susanti, Hevi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In the context of education, especially in pesantren, interpersonal communication plays a key role in shaping the character of santri. Pesantren as an Islamic-based educational institution aims to develop individuals who have faith, noble character, and relevant life skills. Coaches in pesantren not only function as teachers but also as moral and character mentors for students. Through daily interactions with students, coaches help instill religious and ethical values that shape their character. The purpose of this study is to analyze Interpersonal communication between coaches and students in the formation of students' self-character in Al-Azkiya Islamic boarding school. This research uses descriptive qualitative method. The research subjects were 6 people, 3 coaches, and 3 santri and were selected using Purposive technique. The results of this study indicate that the effectiveness of interpersonal communication of openness, empathy, supportive attitude, equality and positive attitude together creates an educational environment conducive to the formation of the character of students with integrity, morality, and responsibility. Character education implemented through various activities both in the classroom, extracurricular, and habituation in the dormitory is effective in shaping the positive character of students. These activities not only support the development of religious character but also improve students' academic achievement.